Ketogenic diet may be a new approach to treatment stress urinary incontinence in obese elderly women: report of five cases - Yu Sun; Haixia Chen; Yueran Bai; Tingyue Zhang; Wenpei Bai; Bo Jiang (BMC, 2022)
Abstract Background Stress urinary incontinence (SUI) as a serious social problem restricted women's daily life and affect their quality of life, especially for obese women. The mechanism of stress urinary incontinence is unclear. Weight loss is the first line of treatment for stress incontinence in obese women. Ketogenic diet is a special diet with high fat, low carbohydrate and moderate protein, which can reduce body mass faster than the traditional diet. There exist no reports on the therapeutic effect of ketogenic diet on SUI in obese women. Case presentation Five postmenopausal obese women are diagnosed as mild to moderate stress urinary incontinence, which affected their quality of life for medical treatment. After 4 weeks ketogenic diet, we found that ketogenic diet can significantly improve urine leakage, reduce body weight, decrease visceral fat area, reduce body fat percentage, and reduce BMI. Conclusion Reports in this case reveal that ketogenic diet may become one of the effective methods for the treatment of stress urinary incontinence in obese women in the future, providing a minimally invasive, highly profitable and highly compliant treatment for stress urinary incontinence in obese women.